Metode Kritik Hadis Orientalis - Farid Adnir (SHAHIH (Jurnal Ilmu Kewahyuan), 2021)
The purpose of this journal was made so that we can know the actions of the orientalists in criticizing the Hadith of the Prophet Muhammad, how the criticism submitted by the orientalists has various shortcomings and on that basis, we must see how the hadith among Muslim scholars occupies a very sacred position, so that their research on the validity of hadith is driven by the central role played by hadith as a source of law and theological doctrine. In contrast to western scholars (orientalists) or often termed outsiders, for them studying hadith is not based on theological doctrines but driven by historical interest. For example when studying Islamic law, they tend to approach it as a model of thought rather than a collection of rights, duties and rules. -cultural, although it is not evident from its subjectivity as an outsider. So for the reasons above we need to see how the orientalists criticize the hadith of the Prophet Muhammad